Religiosity and Its Impact on Energy Consumption in Indonesian Muslim Households - Arkania Choirin Tameema; Djoni Hartono; Misdawita (Jurnal Ekonomi Pembangunan, 2026)
This study examines the underexplored relationship between religiosity and household energy consumption, applying religious behavior theory to energy economics in Indonesia—the world’s largest Muslim-majority nation. While traditional models focus on socioeconomic determinants, this paper investigates how Islamic values influence electricity consumption, explicitly addressing the inherent endogeneity of self-reported religiosity. Utilizing data from the Indonesian Family Life Survey (IFLS-5) comprising 21,023 Muslim households, we employ a two-stage least squares (2SLS) instrumental variable approach, proxying religiosity through ritual frequency and religious practices to overcome omitted variable and self-selection biases. The empirical results reveal a robust, statistically significant negative relationship between higher levels of religiosity and household electricity expenditure. This finding aligns with the theoretical framework that religious tenets foster moderation, self-control, and environmental stewardship. The results remain resilient across extensive sensitivity analyses and alternative model specifications. Culturally, these findings imply that faith-based institutions and religious leaders are powerful, cost-effective conduits for behavioral energy conservation. Integrating moral paradigms into national climate strategies offers a potent, localized mechanism to complement standard efficiency policies and accelerate carbon emission reductions in emerging Muslim-majority economies.